Effects of Bout Duration on Load, Sprint, and Jump Ability During a One-on-one Transition Task - Asian-Clemente, Jose; Rabano-Munoz, Alberto; Requena, Bernardo; Suarez-Arrones, Luis (International Journal of Sports Medicine, 2023)
This study examined the training load on professional soccer players during transition games performed with different bout durations and their effects on speed and jump tests. Fourteen young soccer players played a transition game of different bout durations: 15 (TG15), 30 (TG30), and 60 (TG60) seconds. Total distance covered (DC), accelerations and decelerations above 1.0 and 2.5 m·s-2, rate of perceived exertion (RPE), maximal heart rate (HRmax) and above 90% (HR>90), distance covered between 18.0–20.9 km·h-1 (DC 18.0–20.9 km·h-1), 21.0–23.9 km·h-1 (DC 21.0–23.9 km·h-1), above 24.0 km·h-1 (DC>24.0 km·h-1), peak speed, sprint profile, sprint, and countermovement jump tests were recorded. TG15 obtained greater DC, DC>21.0 km·h-1, Player load, Acc>2.5 m·s-2 than TG30 and TG60 (p<0.01) and Acc<2.5 m·s-2, Dec>2.5 m·s-2 than TG60 (p<0.01). TG30 showed more HR>90 and RPE (p<0.01) than TG15, and DC, DC>18.0 km·h-1, Player load, Acc>2.5 m·s-2, Dec>2.5 m·s-2, HR>90 and RPE than TG60 (p<0.01 and<0.05). Transition games showed lower sprint and jump results after the intervention (p<0.01). Bout duration has been configured as an important constraint that influences the transition games and the performance of soccer players.
Keywords: time-motion; sided-games; performance; football; speed